The Influence of Destination Image, Emotional Experience, and Perceived Value on Tourist Loyalty Through Satisfaction as an Intervening Variable (Jurnal Manajemen Bisnis, 2026)
This study aims to analyze the influence of destination image, emotional experience, and perceived value on tourist loyalty through tourist satisfaction as an intervening variable on Talang Siring Beach tourism, Pamekasan. The method used in this study is quantitive. The data collection technique used a questionnaire of 97 respondents based on the Cochran formula, this study involved all visitors to Talang Siring Beach, Pamekasan as the research population. The collected data were analyzed using SEM-PLS through SmartPLS. This study found that all hypotheses statistically showed a positive and significant influence between destination image, emotional experience, and perceived value on tourist loyalty. This finding emphasizes the importance of managing destination image, emotional experience, and perceived value to strengthen tourist loyalty.